PENGELOLAAN PEMBELAJARAN DI HOMESCHOOLING PRIMAGAMA MAKASSAR - Wahyu Sandi Setiawan; Andi Nurochmah; Sumarlin Mus (Jurnal Administrasi, Kebijakan, dan Kepemimpinan Pendidikan (JAK2P), 2023)
The purpose of this study was to describe the management of Homeschooling Primagama Makassar learning. The approach used is quantitative with a descriptive format. The research location is in Makassar City, located on Jalan Domba No. 42. This research uses interview, observation and documentation study data collection techniques. Checking the validity of the data used is source triangulation and method triangulation. Data analysis techniques were carried out through data reduction, data presentation and drawing conclusions or verification. The results obtained from this study are the management of learning at Homeschooling Primagama Makassaar in accordance with learning management standards which can be seen from the lesson planning including planning the formulation of learning objectives at Homeschooling Primagama Makassar, always involving the school and teachers in learning planning such as the application of methods final trip learning, study tour and welcoming class. As well as the implementation of learning carried out in terms of implementing learning at Homeschooling Primagama Makassar, that starting from opening the learning process, learning materials and supporting and inhibiting factors to closing lessons at Homeschooling Primagama Makassar carried out in accordance with teacher competency standards, as well as to improve the quality of learning at Homeschooling Primagama Makassar, always strives for ways to teach teachers in both adaptive subjects.